Relationship Between Entrepreneurial Orientation and Business Performance in MSMEs: The Mediating Role of Market Orientation - Eko Boedhi Santoso; Fatkhur Rochman; Izzatul Ulya (University of Merdeka Malang, 2025)
Micro, small, and medium enterprises (MSMEs) operating in the processed food sector have great potential in supporting the local economy, but still face challenges in improving competitiveness and business performance, especially related to innovation, market response, and mastery of business strategies. This phenomenon indicates the need for more adaptive and responsive managerial strategies, particularly through entrepreneurial and market orientation approaches. This study uses a quantitative approach with an explanatory design, data were collected through a census technique using questionnaires from 51 MSME entrepreneurs and analyzed using SEM-PLS with the help of the SmartPLS application. The research results show that entrepreneurial orientation has a positive and significant effect on business performance. Additionally, market orientation also has a direct influence on business performance while partially mediating the relationship between entrepreneurial orientation and business performance. These findings recommend the importance of integrating entrepreneurial spirit and market understanding as a strategy to enhance the performance and sustainability of SMEs amidst increasingly competitive competition.